A Study of PVD Bi-Layer Cutting Tool Coatings Used for Machining of Super Duplex Stainless Steel - Monteiro Lima, Lucas (My University, 2020)
The oil and gas industry places intensive demands on materials due to the corrosive environments they work in and the heavy loads and wear conditions they apply. Materials such as Super Duplex Stainless Steel (SDSS) are widely used for this purpose, since their chemical composition, corrosion resistance and mechanical properties enable them to sustain the severe conditions associated with petroleum extraction. However, machining this material presents a significant challenge due to the high temperatures and stresses generated during the cutting process, which result in rapid tool wear. To address this challenge, a series of Physical Vapour Deposition (PVD) bi-layer multifunctional coatings were developed to improve tool performance during SDSS machining. Bi-layer coatings consist of two layers, each of which is designed to address various wear phenomena observed during machining. In addition, the cutting performance of the latest generation of PVD coating deposition methods known as High-Power Impulse Magnetron Sputtering (HiPIMS) was evaluated. This study investigated the effect of different HiPIMS bi-layer coatings on the wear performance of cutting tools during finish turning of SDSS.
Keywords: machining; super duplex stainless steel; coating; sdss